2020
DOI: 10.1094/pdis-02-19-0353-re
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Thiophanate-Methyl in Botrytis cinerea Isolates From Californian Vineyards and Pistachio and Pomegranate Orchards

Abstract: In this study, a mycelial growth assay was used to evaluate the sensitivity to thiophanate-methyl of 144 Botrytis cinerea isolates (collection A) from Californian vineyards and pistachio and pomegranate orchards. Based on the effective concentration that inhibits 50% of growth (EC50) values for mycelial growth inhibition on fungicide-amended media, 3, 28, 10, and 58% of the isolates showed sensitivity (SS; EC50 < 1 µg/ml), low resistance (LR; 1 < EC50 < 10 µg/ml), weak resistance (WR; 10 < EC50 <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The selected isolates exhibited EC50 values ranging from 0.012 to over 800 ppm for carbendazim and 0.948 to over 1280 ppm for thiophanate-methyl. Previous studies have also reported the existence of isolates with high EC50 values that can withstand high fungicide concentrations [6,10,17,18]. The mutation in the β-tubulin gene has been found to be responsible for resistance to MBC fungicides, and the effects of this mutation have been examined by several researchers [11,16,19,20].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The selected isolates exhibited EC50 values ranging from 0.012 to over 800 ppm for carbendazim and 0.948 to over 1280 ppm for thiophanate-methyl. Previous studies have also reported the existence of isolates with high EC50 values that can withstand high fungicide concentrations [6,10,17,18]. The mutation in the β-tubulin gene has been found to be responsible for resistance to MBC fungicides, and the effects of this mutation have been examined by several researchers [11,16,19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Different levels of resistance were found in the isolates towards carbendazim and thiophanate-methyl. Avenot et al [10] reported that mutations in β-tubulin gene regions associated with high levels of Botrytis resistance to thiophanate-methyl were not related to low levels of resistance. In the present study, isolates with low levels of resistance to thiophanate-methyl in the EC50 test exhibited the pattern of sensitive isolates in PCR-RFLP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations